Tìm hiểu các phương pháp tiếp cận đánh giá chất lượng dịch vụ thông tin-thư viện - Bùi, Thị Thanh Diệu (Cục Thông tin khoa học và công nghệ quốc gia, 2023)
The article provides an overview on different methodologies for evaluatingthe quality of information-library services that have been applied internationally and locally. By analyzing the literature, the article discusses advantages and disadvantages of each approach.